2010
DOI: 10.1002/ibd.21051
|View full text |Cite
|
Sign up to set email alerts
|

Does primary sclerosing cholangitis impact quality of life in patients with inflammatory bowel disease?

Abstract: PSC does not seem to influence disease-specific HRQoL in our patients with IBD but is associated with a higher rate of work disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 26 publications
4
23
0
2
Order By: Relevance
“…A total of 213 participants had a low adherence score (36.2%), 199 medium adherence (33.8%) and 176 high adherence (29.9%). Mean quality of life as measured by the SIBDQ score was 51 (SD=11.1), which is consistent with reported means for mild or inactive IBD(2, 10, 21, 22). Mean short Crohn’s Disease Activity Index was 52.1, indicating inactive disease.…”
Section: Resultssupporting
confidence: 84%
“…A total of 213 participants had a low adherence score (36.2%), 199 medium adherence (33.8%) and 176 high adherence (29.9%). Mean quality of life as measured by the SIBDQ score was 51 (SD=11.1), which is consistent with reported means for mild or inactive IBD(2, 10, 21, 22). Mean short Crohn’s Disease Activity Index was 52.1, indicating inactive disease.…”
Section: Resultssupporting
confidence: 84%
“…To create a homogeneous group of patients, the inclusion criteria were stringent. We excluded patients with abnormal liver tests or known liver diseases to avoid basal perturbations of BA biosynthesis, which may be observed—for example, in cholestatic diseases, such as primary sclerosing cholangitis (often associated with IBD) 33 34. As the terminal ileum is the site of BA reabsorption,35–37 CD patients with ileal involvement were also excluded by principle.…”
Section: Discussionmentioning
confidence: 99%
“…In a small, retrospective, case–control study, the presence of PSC in patients with IBD did not significantly impair HRQOL but was associated with higher rate of work disability . However, two more recent and larger studies demonstrated a significant association between PSC and impaired HRQOL .…”
Section: Primary Sclerosing Cholangitismentioning
confidence: 85%